Evaluation of [18F]BR420 and [18F]BR351 as radiotracers for MMP‐9 imaging in colorectal cancer. (21st December 2016) - Vazquez, Naiara; Missault, Stephan; Vangestel, Christel; Deleye, Steven; Thomae, David; Van der Veken, Pieter; Augustyns, Koen; Staelens, Steven; Dedeurwaerdere, Stefanie; wyffels, Leonie
Abstract : MMP‐9 is a zinc‐dependent endopeptidase that is involved in the proteolytic degradation of the extracellular matrix and plays an important role in cancer migration, invasion, and metastasis. The aim of this study was to evaluate the potential of MMP‐tracers [ 18 F]BR420 and [ 18 F]BR351 for MMP‐9 imaging in a colorectal cancer xenograft model. [ 18 F]BR420 and [ 18 F]BR351 were synthesized using an automated synthesis module. For [ 18 F]BR420, a novel and improved radiosynthesis was developed. Plasma stability and MMP‐9‐targeting capacity of both radiotracers was compared in the Colo205 colorectal cancer model. MMP‐9 and MMP‐2 expression levels in the tumors were evaluated by immunohistochemistry and in situ zymography. μPET imaging as well as ex vivo biodistribution revealed a higher tumor uptake for [ 18 F]BR420 (3.15% ± 0.03% ID/g vs 0.94% ± 0.18% ID/g for [ 18 F]BR351 at 2 hours pi) but slower blood clearance compared with [ 18 F]BR351. [ 18 F]BR351 was quickly metabolized in plasma with 20.28% ± 5.41% of intact tracer remaining at 15 minutes postinjection (PI). By contrast, [ 18 F]BR420 displayed a higher metabolic stability with >86% intact tracer remaining at 2 hours PI. Immunohistochemistry revealed the presence of MMP‐9 and MMP‐2 in the tumor tissue, which was confirmed by in situ zymography. However, an autoradiography analysis of tracer distribution in the tumors did not correlate with MMP‐9 expression. [ 18 F]BR420 displayed a higher tumor uptake and higher stability compared with [ 18 F]BR351 but a low tumor‐to‐blood ratio and discrepancy between tracer distribution and MMP‐9 immunohistochemistry. Therefore, both tracers will not be usefulness for MMP‐9 imaging in colorectal cancer. Abstract : Promising radiofluorinated MMP inhibitors [ 18 F]BR420 and [ 18 F]BR351 were evaluated for MMP‐9 imaging in a colorectal cancer model. Low tumor uptake and plasma instability were demonstrated for [ 18 F]BR351. By contrast, [ 18 F]BR420 showed higher tumor uptake but with a low tumor‐to‐blood ratio and discrepancy between tracer distribution in the tumor and MMP‐9 immunohistochemistry. We therefore envisage both tracers to be not useful for specific MMP‐9 imaging in colorectal cancer.